Phosphorus adsorption characteristics and release risk in saline soils: a case study of Songnen Plain, China - Jiang, Yan; Yan, Qiuliang; Liu, Tonglinxi; Xu, Yifan; Han, Xing; Ma, Xiulan; Wang, Yujun (Frontiers in Plant Science, 2023)
The Songnen Plain is one of the three major saline-alkali areas in China, covering a vast area, where drought and overgrazing have exacerbated the salinization trend, and will have great potential for development if utilized rationally.Phosphorus, as one of important soil nutrients, plays a crucial role in plant growth.How to minimize its loss and migration has become a current research hotspot. The objective of the present study was to elucidate the adsorption properties of phosphorus in soils affected by salinization and to establish the correlation between the potential for phosphorus release and soil properties.Methods:A batch treatment test was conducted in this study using three soils with the various salinization degrees to examine the impact of environmental factors on the adsorption properties and potential release of phosphorus.Results and discussion:It was found that the maximum phosphorus adsorption by the three salinization soils in 0-360 minutes accounted for 86.8%-90.5% of the total adsorption capacity; the equilibrium adsorption capacity was: HS> MS> LS. In cases where the phosphorus level in the surrounding liquid is low, the three levels of salinized soils exhibited varying levels of phosphorus discharge, with the adsorbent acting as the origin of contaminants. The Pseudo-second-order model kinetics and Langmuir equation can well describe the adsorption process ， and the adsorption process is spontaneous heat absorption with entropy increase. Increasing the pH led to an increase in the adsorption of phosphorus from the three salinized soils.Additionally, the adsorption was enhanced by introducing varying concentrations of Na + , Ca 2+ , and Al 3+ to the background solution. The phosphorus eutrophication release risk (ERI) demonstrated a gradual decline as temperature increased. Correlation analysis revealed a noteworthy positive correlation between TN, TP, and ERI , as well as a significant negative correlation between CEC, K + , and ERI . Furthermore, there was a highly significant negative correlation between coarse silt and fine silt.Considering local climatic and environmental factors is crucial for controlling the adsorption capacity of phosphorus in various salinized soils, as it can unveil the mechanism of phosphorus adsorption and impact its migration and release risk.